Assessing Performance and Mechanics of the PUCP IArm Upper Limb Prosthesis - MacEdo, E.; Romero, E.; Abarca, V.E.; Elías, D.A. (Springer Science and Business Media Deutschland GmbH, 2025)
Access to upper limb prostheses in developing countries, including Peru, is constrained. Models with features like increased individual finger strength and greater degrees of freedom tend to be costly, compelling individuals to opt for less advanced passive prostheses or aesthetic options. This creates a significant necessity for affordable prosthetics that do not compromise essential functionality and allow users to perform daily activities effectively. An example of this development is the PUCP IArm prosthesis, a laboratory model designed and developed at the “Pontificia Universidad Católica del Perú” (PUCP, for its initials in Spanish). This functional and accessible prosthesis is manufactured using additive manufacturing technologies. This study aims to characterize the mechatronic properties and evaluate the functionality of the hand component of the PUCP IArm prosthesis. Evaluations included videogrammetric assessments, finger force measurements, distal tensile tests, static downward bending tests, and response latency measurements between gesture detection and actuation. The assessed prosthesis weighs 230 g and has a maximum load capacity of 1.83 N in pinch gestures and 19.05 N in cylindrical grip. Compared with myoelectric activation prosthesis models developed using digital fabrication techniques, the results obtained by the PUCP IArm prosthesis are promising and stand out.
Keywords: Prosthesis; Mechanics; Engineering; Materials science; Medicine; Computer science; Physics; Surgery; https://purl.org/pe-repo/ocde/ford#2.09.00